Does Low-Dose Aspirin Initiated Before 11 Weeks' Gestation Reduce the Rate of Preeclampsia?. Issue 10 (October 2020) - Chaemsaithong, Piya; Cuenca-Gomez, Diana; Plana, María N.; Gil, María M.; Poon, Liona C.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;222(5):437–450) Low-dose aspirin has been shown to decrease the rate of preterm preeclampsia in women identified as high risk. The ASPRE (Combined Multimarker Screening and Randomized Patient Treatment with Aspirin for Evidence-Based Preeclampsia Prevention) trial found that high-risk women who received aspirin versus placebo saw a substantially reduced rate of preterm preeclampsia.